Mostly Mississippi : A Very Damp Adventure - Speakman, Harold, 1888-1928 (Book collections on Project MUSE., 2004)
A classic American travel narrative that captures the soul of the river, Mostly Mississippi features lyrical descriptions of encounters with archetypal characters, landscapes, and experiences. The Speakmans meet lumberjacks in northern Minnesota and Mormo.